A vascular smooth muscle-specific integrin-α8 Cre mouse for lymphatic contraction studies that allows male-female comparisons and avoids visceral myopathy - Davis, Michael J.; Kim, Hae Jin; Li, Min; Zawieja, Scott D. (Frontiers in Physiology, 2023)
Introduction: The widely-used, tamoxifen-inducible, smooth muscle (SM)-specific Cre, Myh11-CreERT2, suffers from two disadvantages: 1) it is carried on the Y-chromosome and thus only effective for gene deletion in male mice, and 2) it recombines in both vascular and non-vascular SM, potentially leading to unwanted or confounding gastrointestinal phenotypes. Here, we tested the effectiveness of a new, SM-specific Cre, based on the integrin α8 promoter (Itga8-CreERT2), that has been recently developed and characterized, to assess the effects of Cav1.2 deletion on mouse lymphatic SM function. Methods:Cav1.2 (the L-type voltage-gated calcium channel) is essential for lymphatic pacemaking and contraction and its deletion using either Myh11-CreERT2 or Itga8-CreERT2 abolished spontaneous lymphatic contractions. Mouse lymphatic contractile function was assessed using two ex vivo methods. Results:Myh11-CreERT2; Cav1.2f/f mice died of gastrointestinal obstruction within 20 days of the first tamoxifen injection, preceded by several days of progressively poor health, with symptoms including weight loss, poor grooming, hunched posture, and reduced overall activity. In contrast, Itga8-CreERT2; Cav1.2f/f mice survived for >80 days after induction and were in normal health until the time of sacrifice for experimental studies. Cav1.2 deletion was equally effective in male and female mice. Discussion: Our results demonstrate that Itga8-CreERT2 can be used to effectively delete genes in lymphatic smooth muscle while avoiding potentially lethal visceral myopathy and allowing comparative studies of lymphatic contractile function in both male and female mice.